Measure: In Pursuit of Musical Time - Moskovitz, Marc D. (Woodbridge Boydell, 2022)
Follows the fascinating story of musical timekeeping, beginning in an age before the existence of external measuring devices and continuing to the present-day use of the Smartphone app.The book opens with an exploration of musical time keeping as expressed in the artwork and musical writing of the Renaissance, sources that inform our early understanding of an age when music making was bound up with motions of the body and the pulsing of the human heart. With the adoption of the simple pendulum and the subsequent incorporation of tempo-related language, musicians gained the ability to communicate concepts of speed and slowness with ever-increasing precision. The seventeenth and eighteenth centuries witnessed the development of a diverse array of musical time-keeping devices, yet it was not until the nineteenth century that a single device combined the critical elements of accuracy, functionality and affordability.Enter the metronome: portable and affordable, a triumph of innovation that enabled musicians to establish and faithfully reproduce musical time with accuracy and ease. From Beethoven to Ligeti, Moskovitz looks to a number of distinguished composers who used or refused this revolutionary machine and explores the complicated relationship that unfolded between the metronome, the musical world and practitioners in other disciplines who sought to exploit its potential.
Keywords: Tobacco; Metronome; Music history